Assessing the Ecological Water Level: The Case of Four Mediterranean Lakes - O. Petriki; D. Zervas; C. Doulgeris; D. Bobori (2020)
Petriki, O., D. Zervas, Ch. Doulgeris, D. Bobori. 2020. Assessing the Ecological Water Level: The Case of Four Mediterranean Lakes. Water: 12, 2977. doi:10.3390/w12112977